2017
DOI: 10.1038/srep41136
|View full text |Cite
|
Sign up to set email alerts
|

Biological Membrane-Packed Mesenchymal Stem Cells Treat Acute Kidney Disease by Ameliorating Mitochondrial-Related Apoptosis

Abstract: The mortality of rhabdomyolysis-induced AKI remains high because no effective therapy exists. We investigated a new therapeutic method using MSCs. The aim of this study was to investigate the therapeutic potential and anti-apoptotic mechanisms of action of MSCs in the treatment of AKI induced by glycerol in vivo and in vitro. We used Duragen as a biological membrane to pack MSCs on the glycerol-injured renal tissue in vivo. The anti-apoptotic mechanism was investigated. In vitro, HK-2 cells were incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…2010 ), anti-inflammatory ( Ueki et al . 2013 ), anti-apoptotic ( Geng et al . 2017 ) and antibacterial ( Mun et al .…”
Section: Discussionmentioning
confidence: 99%
“…2010 ), anti-inflammatory ( Ueki et al . 2013 ), anti-apoptotic ( Geng et al . 2017 ) and antibacterial ( Mun et al .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental AKI induced by glycerol injection is the most commonly used experimental model of RM 1 , 11 , 12 and is characterized by intense cortical acute tubular necrosis and inflammatory cell infiltration 13 . Curcumin is an active component in turmeric rhizomes ( Curcuma Longa Linn ), and is a polyphenolic curcuminoid that accounts for 3–5% of turmeric 14 which has been shown to have antioxidant 15 – 18 , anti-inflammatory 19 – 21 , anti-apoptotic 22 and anti-bacterial 23 functions. The role of curcumin as a protective agent against renal injury induced by gentamicin, contrast agent, cisplatin and diabetes has been previously investigated 24 – 32 .…”
Section: Introductionmentioning
confidence: 99%
“…A common complication of cisplatin administration is AKI [ 28 ]. PTEN acts as a tumor suppressor by negatively regulating the PI3K signaling pathway, which plays an important role in AKI [ 29 , 30 , 31 ], and studies have indicated that PTEN is involved in the mechanism of AKI [ 8 , 32 ]. However, the role of PTEN in cisplatin-induced AKI is unknown.…”
Section: Discussionmentioning
confidence: 99%